2006
DOI: 10.1080/17452750600763947
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-intrusive operator logging to support the analysis and generation of product engineering data using immersive VR

Abstract: Abstract:Virtual reality (VR) has the potential to substantially alter the manner in which products of the future are engineered. Currently there are many applications of VR during the product engineering process from design and analysis through to process planning, assembly, machining and shop floor layout. VR takes a multitude of forms, including immersive, desktop, augmented, and is rapidly developing as a tool that can be used in the engineering of products.This paper looks at the use of immersive VR as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…immersive, virtual environments and haptic devices. Ritchie et al [41,42] presented an early prototype proving that immersive VR as a non-intrusive user logging tool can be used effectively for capturing expert knowledge and the generation of instruction plans or guides in product engineering tasks, i.e. product assembly planning.…”
Section: User Logging and Engineering Knowledge Capturementioning
confidence: 99%
“…immersive, virtual environments and haptic devices. Ritchie et al [41,42] presented an early prototype proving that immersive VR as a non-intrusive user logging tool can be used effectively for capturing expert knowledge and the generation of instruction plans or guides in product engineering tasks, i.e. product assembly planning.…”
Section: User Logging and Engineering Knowledge Capturementioning
confidence: 99%
“…Logging and the reuse of the associated information as an engineering task analysis tool within virtual environments is central to this work; indeed, the application of these methods is similar to those applied by Ritchie et al in a number of engineering task analysis applications covering both design and manufacturing assembly processes as well as early knowledge acquisition [13].…”
Section: Introductionmentioning
confidence: 96%
“…However, one of the major but less well known advantages of VR technology pertains to data logging. For engineering purposes, logging the user provides rich data for downstream use to automatically generate designs or manufacturing instructions, analyse design and manufacturing tasks, map engineering processes and, tentatively, acquire expert knowledge (Ritchie et al, 2006). The authors feel that the benefits of VR in these areas have not been fully disseminated to the wider industrial community and -with the advent of cheaper PCbased VR solutions -perhaps a wider appreciation of the capabilities of this type of technology may encourage companies to adopt VR solutions for some of their product design processes.…”
Section: Introductionmentioning
confidence: 99%
“…The logging and reuse of associated information as an engineering task analysis tool within haptic VR environments is central to this work; indeed, the application of these methods is similar to a number of engineering task analysis applications covering both design and manufacturing assembly processes as well as early knowledge acquisition (Ritchie et al, 2006). Following a successful pilot study by Lim et al (2006), while statistically inconclusive, it has shown that Design for Assembly (DFA) components had an impact on task completion time in the virtual environment.…”
Section: Introductionmentioning
confidence: 99%